The Relationship Between Pregnant Women's Knowledge About Antenatal Care and Their Antenatal Visit Behavior in the Working Area Public Health Center Bekasi - Sari, Leni Permata; Sunirah, Sunirah; Puspitasari, Indah; Shoaliha, Maratun; Irwanto, Moh. Firman (Nursing Genius Journal, 2025)
Low levels of knowledge about Antenatal Care (ANC) among pregnant women contribute to reduced participation in antenatal visits. Adequate knowledge is expected to strongly motivate pregnant women to take care of themselves and their pregnancies by adhering to the advice provided by antenatal care providers. Objective: This study aims to examine the relationship between pregnant women's knowledge about ANC and their antenatal visit behavior.Methods: This research employed a descriptive quantitative design with a cross-sectional approach. The study population consisted of 104 respondents, selected through accidental sampling. The variables analyzed included pregnant women's knowledge about ANC, their antenatal visit behavior, and family support.Results: The highest proportion of respondents demonstrated good knowledge about ANC (95.2%). A majority also exhibited good antenatal visit behavior (78.8%), and most received moderate family support (83.7%). Conclusion: The study findings indicate a positive relationship between pregnant women's knowledge of ANC and their antenatal visit behavior at the Karang Kitri Public Health Center in Bekasi City, with a generally favorable outcome.